Conceptual similarity and visual metaphor: effects on viewing times, appreciation, and recall - Lagerwerf, Luuk; Van Mulken, Margot; Lagerwerf, Jefta B. (Frontiers in Communication, 2023)
Different levels of conceptual similarity in equivalent visual structures may determine the way meaning is attributed to images. The degree to which two depicted objects are of the same kind limits interpretive possibilities. In the current research, visual hyponyms (objects of the same kind) were contrasted with visual metaphors and unrelated object pairs. Hyponyms are conceptually more similar than metaphor's source and target, or two unrelated objects. Metaphorically related objects share a ground for comparison that lacks between unrelated objects. We expected viewers to interpret hyponyms more quickly than metaphors or unrelated objects. For liking, there were competing predictions: hyponyms are appreciated more because they are easier, or metaphors are liked more because successful cognitive effort is rewarded. In the first experiment viewers were asked to identify relationships in 27 object pairs. Hyponyms were identified faster than metaphors and metaphors faster than unrelated objects. In the second experiment, with the same materials, viewers were asked to rate appreciation for each object pair. This reduced viewing times substantially. Appreciation was higher for hyponyms than for visual metaphors. In a third experiment with the same materials, exposure duration was varied. Hyponyms were preferred to metaphors and unrelated objects irrespective of exposure duration. Gewijzigde veldcode heeft opmaak toegepast: Lettertype: (Standaard) +Koppen CS (Times New Roman), Complex scriptlettertype: +Koppen CS (Times New Roman)Conceptual similarity and visual metaphor 2019)(Gibbs Jr 2011). Although these frameworks claim to be universal, they have rarely been applied to other domains, in this case, the visual domain.In the field of advertising, on the other hand, visual metaphors have been the subject of study on many occasions, and the focus is on appreciation, not on understanding (McQuarrie and Mick 1999;